Reinterpreting the Qur'anic Concept of Poverty: A Novel Hermeneutical Reading of the Term Miskīn in Al-Baqarah (2:184) through Paul Ricoeur's Perspective - Rifki, Mohammad Maulana Khoirur; Laily, Istiharokum; Pangestu, Satrio Anugrah (Universitas Muhammadiyah Surakarta, 2025)
This research departs from the urgency of understanding poverty not only as an economic issue, but also as a multidimensional phenomenon that is full of social and spiritual meaning in an Islamic perspective. This study aims to reinterpret the term